(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This research scrutinizes the income determinants of resettled exiles in the United States using data from the 2022 Annual Survey of Refugees (ASR) with 1,152 participants. The anylize applies Ordinary Least Squares (OLS) retrogression and variable selection via the Least Absolute Shrinkage and Selection Operator (LASSO).The analysis reveal that the strongest predictor of income is the country-of- origin income level, where displaced persons from upper-middleincome countries earn 68.2% furtherthan those from low-income nations (p < 0.001). Education is a meaningful factor, with the highest returns seen among those holding a bachelor’s degree (69.9%).A gender gap persists, with women earning 12.5% less than men. The 51–60 age group shows a significant lower in income (-27.3%), and more recent arrivals earn 14–16% less, recommending a gradual way for economic adjustment .The research suggests that refugee income is influenced by human capital, pre-migration factors, and rules for joining together, calling for enhanced credential recognition and employment policies that respect gender.